Pelatihan Pembuatan Konektor Masker Untuk Meningkatkan Pendapatan Ibu-Ibu Pkk Dimasa Pandemi Covid-19 Didesa Sukaraya Kecamatan Baturaja Timur Kabupaten Ogan Komering Ulu - Rini Apriyani; Sally Maria Bramana; Hema Malini (AMMA : Jurnal Pengabdian Masyarakat, 2022)
This community service activity aims to provide training/counseling for PKK mothers in Sukaraya Village, Baturaa Timur District in helping and developing strong entrepreneurial creativity and innovation so that they can survive in creativity during this covid 19 pandemic. Held on June 15, 2021. The training process was held with a learning method approach, namely demos, lectures - questions and answers. This activity involved lecturers and students of STIE Dwi Sakti Baturaja in collaboration with PKK women, totaling 42 people who attended this activity. Based on the results of the evaluation of these activities, the enthusiasm of the participants during the training/extension was quite high. This can be seen from the seriousness of the participants in participating in the training and inviting the implementing team to join again in providing retraining in a different theme. With this training, it is hoped that participants will be able to implement the knowledge gained so that young people who are classified as students can carry out creativity and entrepreneurial innovation that are outside normal ways to be motivated and not feel bored with the current situation in a long pandemic.